Impacto de los microcréditos en la reducción de la vulnerabilidad en la ciudad de Loja - Tacuri, Lorena del Cisne (2017)
The present study aims to develop an analysis on the social impact of microfinance in vulnerable sectors, in thecontext of existing financial institutions in our country, and to analyze the prospects of impact, both in the economic area and its financial sustainability in the year 2016 as in the social space. By means of a comparative analysis with the application of an exploratory investigation and with the use of the technique of the interview to the 16 cooperatives of savings and credit that directly affect in these sectors and 349 surveys determining the result through the formula of the sample and Applied to the segment of vulnerable sectors by the random method; This is how the literature review has generated clues about the incidence of microfinance in vulnerable sectors. The purpose of this article is to determine how microfinance experiences a significant impact on the social aspect, with the expansion of its coverage, constant turnover of the microcredit product and perfecting its services, thus demonstrating its capacity for adaptation and change despite the different phenomena Economic and social problems that have been affected in recent years.